Clinical approbation today: analysis of current problems and solutions - V. V. Omelyanovskiy; D. V. Lukyantseva; T. I. Alekseeva; Yu. V. Voropaeva; T. A. Tomilina; R. A. Teryan; A. O. Gadzhieva (Фармакоэкономика, 2023)
Objective: description of the current problems concerning the development and conducting of a protocol of clinical approbation (CA) of methods of prevention, diagnosis, treatment and rehabilitation to optimize the implementation of innovative medical technologies in practical health care through CA.Material and methods. The review of the legislative framework governing CA and analysis of the proceedings of CA issues strategic session were carried out, management decisions to improve the effectiveness of CA were proposed. Analysis of legal acts stipulating the notion and status of CA was performed. The study included orders of the Ministry of Health of the Russian Federation, which established regulations on the organization of CA, the CA protocol templates, etc. Methodological materials, review articles on the organization of health care in the Russian Federation selected from various open sources were studied. The basis for making management decisions on improving the quality of CA procedure was formed by the participants of the CA issues strategic session which had been initiated by the Center for Healthcare Quality Assessment and Control.Results. Based on the results of the strategic session and the analysis of legal acts, current issues related to CA regulation, such as lack of СА coordination and research publications, poor methodological quality of clinical and economic evaluations within CA, promotion of innovation through CA were identified. The developed managerial decisions on improvement of CA and promotion of innovations in practical health care were presented.Conclusion. Current legal acts regulating CA activities should be updated with a view to establishing a transparent system of clinical and economic evaluations of new and innovative methods for making an informed decision to include them in clinical guidelines and routine clinical practice. It is proposed to legally assign the functions of CA coordinator to the federal medical development organizations. Regarding the promotion of innovative technologies in practical health care, it is advisable to create a system for the introduction of innovations, including taking into account conducting CA.